Online Sexual Partner Seeking as a Social Practice: Qualitative Evidence from the 4th British National Survey of Sexual Attitudes and Lifestyles (Natsal-4). Issue 8 (13th October 2022) - Reid, David S; Macdowall, Wendy G.; Lewis, Ruth; Hogan, Bernie; Mitchell, Kirstin R.; Bosó Pérez, Raquel; Gibbs, Jo; Smith, Clarissa; Attwood, Feona; Mercer, Catherine H.; Sonnenberg, Pam; Bonell, Chris
ABSTRACT: Once perceived as a means for those unsuccessful at traditional dating, online dating has become normalized as a way to seek sexual or romantic partners. In 2019, we interviewed 40 British adults on the role of digital technologies in their sexual lives; this paper draws on the accounts of 22 who had used such technologies for seeking partners. We analyzed qualitative accounts of online partner seeking as a social practice, drawing on a sample diverse in age, gender and sexual orientation, and informed by sexual script and social practice theory. Our theoretically informed analysis emphasized the multiple meanings and goals involved, the affordances of the technology and individuals' skills. Our study provided several novel contributions. Young heterosexual people commonly used general social media, rather than dating apps, to meet partners; meeting partners often involved complex interplays between online and offline networks and encounters. Risks were defined not merely in relation to "risky others" but in terms of one's own actions or attitudes. Participants deployed various skills in minimizing harms such as non-consensual sharing of intimate images, and used self-care skills such as setting limits to engagement.